Peran guru dalam meningkatkan minat belajar metematika siswa - Aisyah11, Siti (Maliki Interdisciplinary Journal, 2026)
Learning interest is an important factor in determining student success, especially in mathematics learning, which is often considered difficult by students. This study aims to describe the teacher’s role in increasing students’ learning interest at school. The method used in this research was interviewing teachers and students. The results of the study show that teachers play a significant role as motivators who encourage students’ enthusiasm for learning. Teachers are required to be innovative in the learning process by connecting the material to everyday life and creating a learning atmosphere that is engaging, enjoyable, and meaningful. In this way, students will not feel difficulties in understanding mathematical concepts and will not feel burdened during the learning process.